2021
DOI: 10.1111/cdev.13553
|View full text |Cite
|
Sign up to set email alerts
|

Values‐Alignment Messaging Boosts Adolescents’ Motivation to Control Social Media Use

Abstract: Two preregistered experiments with 2,733 U.S. high school students (age range = 13-19 years) compared the impact of different messages on adolescents' motivation to control social media use (SMU). A traditional message emphasized the benefits of avoiding SMU, whereas a values-alignment message framed controlling SMU as being consistent with autonomy and social justice. Compared to no message or a traditional message, in both studies, a values-alignment message led to greater motivation to control SMU immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Another single-session classroom-based intervention utilizing cognitive dissonance techniques and SM literacy skills found improved thin ideal internalization one week after the intervention, an effect sustained to the 8-week follow-up, among girls but not boys (Bell et al, 2021 ). Other promising intervention/prevention approaches to reducing problematic SM use, which are not specific to body image but which have preliminary empirical support, include values alignment and mindfulness approaches (Galla et al, 2018 , 2021 ). The coming years will likely see an increase in the number of evidence-based approaches to helping adolescents use SM in ways that align with their values and promote positive well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Another single-session classroom-based intervention utilizing cognitive dissonance techniques and SM literacy skills found improved thin ideal internalization one week after the intervention, an effect sustained to the 8-week follow-up, among girls but not boys (Bell et al, 2021 ). Other promising intervention/prevention approaches to reducing problematic SM use, which are not specific to body image but which have preliminary empirical support, include values alignment and mindfulness approaches (Galla et al, 2018 , 2021 ). The coming years will likely see an increase in the number of evidence-based approaches to helping adolescents use SM in ways that align with their values and promote positive well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the current results highlight possible avenues of intervention to increase adolescents’ positive emotional experiences using social media. Until recently, most social media‐related interventions have focused on limiting social media use directly or reducing the negative effects of social media (e.g., Galla, Choukas‐Bradley, Fiore, & Esposito, 2021; Tamplin, McLean, & Paxton, 2018; Walther, Hanewinkel, & Morgenstern, 2014). Fewer interventions have sought to increase positive experiences on social media or foster the antecedents (e.g., gratitude) of positive social media use.…”
Section: Discussionmentioning
confidence: 99%
“…More recent experimental research demonstrated that teaching adolescents about "addictive" social media designs and their harmful effects can prompt enduring awareness of design features. It can also motivate young people's interest in regulating their social media use and in learning relevant strategies (Galla et al, 2021).…”
Section: Critical Awareness Of Design Features and Psychological Prin...mentioning
confidence: 99%
“…Likely, the value of pledges and media agreements depends on how they are developed and then used. Relevant, too, is the aforementioned experimental research, which demonstrated that education about persuasive tech design featurespresented alongside messages about autonomy and social justicecan boost adolescents' motivation to self-regulate social media use (Galla et al, 2021). Yet these experiments also underscore that motivational changes are no guarantees of lasting behavioral change (Galla et al, 2021).…”
Section: Behavioral Change For Healthy Digital Habitsmentioning
confidence: 99%